PENGEMBANGAN VIDEO INTERAKTIF TARI KREASI DAERAH BERBASIS 5W1H PADA PEMBELAJARAN TEMATIK KELAS IV MADRASAH IBTIDAIYAH - Zulia Nurul Faizah; Siti Rofi'ah (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
The development of interactive videos aims to meet the needs of students in the teaching and learning process in the digital era by utilizing mobile technology. The use of the 5W1H foundation as the basis for compiling materials is a hallmark of the development of this interactive video. This research and development use five stages of ADDIE. Questionnaires, interviews, and documentation were then processed into two types of data, namely qualitative data and quantitative data to then be used as a determinant of the feasibility of interactive videos and to find out the responses of Madrasah Ibtidaiyah students. The 5W1H-based interactive regional dance video has been validated by three expert validators with appropriate criteria and received positive responses from students. Ease of access to products in research and development is a very solution for a more lively and meaningful distance learning model.